PELATIHAN DESAIN GRAFIS MENGGUNAKAN APLIKASI CANVA KEPADA SISWA SD NEGERI 1 SUMBERAGUNG, BOYOLALI - Devi Yunita Saputri; Retno Waluyo; Riyanto; Abdul Azis (Nusantara Hasana Journal, 2023)
Education has a very important role in educating human life and cannot be separated from development and change. The development of technology in this digital era cannot be separated from its influence in the world of education. So that the world of education always adjusts to technological developments as an increase in the quality of education to support educational success. With the Campus Teaching Program, the role of students is needed in assisting the learning process, one of which is in adapting technology to increase student awareness of the importance of technology in today's digital era. Currently, SD Negeri Sumberagung students do not yet have the skills to use the Canva application. The Canva application can be used to create graphic designs so that it can be used to explore students' talents in making graphic designs. There fore it is necessary to conduct graphic design training using the Canva application so that students can use the Canva application to explore their potential to make graphic designs. After training students can use the Canva application, students are very enthusiastic about this activity and students are quite familiar with using the Canva application.